2010
DOI: 10.2134/jeq2009.0140
|View full text |Cite
|
Sign up to set email alerts
|

Regional‐scale Assessment of Soil Salinity in the Red River Valley Using Multi‐year MODIS EVI and NDVI

Abstract: The ability to inventory and map soil salinity at regional scales remains a significant challenge to scientists concerned with the salinization of agricultural soils throughout the world. Previous attempts to use satellite or aerial imagery to assess soil salinity have found limited success in part because of the inability of methods to isolate the effects of soil salinity on vegetative growth from other factors. This study evaluated the use of Moderate Resolution Imaging Spectroradiometer (MODIS) imagery in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 12 publications
(14 reference statements)
4
128
0
Order By: Relevance
“…There has been considerable success in using ground-based geophysical measurements of the apparent soil electrical conductivity (EC a ) to assess salinity across individual fields, including the electrical resistivity (ER) or electromagnetic induction (EM) surveys (e.g., Corwin and Lesch 2003). However, even these methods are currently too time consuming to be applied cost-effectively at regional scales (Lobell et al 2010). Therefore, there is a need for the development of more practical (i.e., quicker and cheaper) methods and tools to determine and evaluate soil salinity in order to improve decision-making processes.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable success in using ground-based geophysical measurements of the apparent soil electrical conductivity (EC a ) to assess salinity across individual fields, including the electrical resistivity (ER) or electromagnetic induction (EM) surveys (e.g., Corwin and Lesch 2003). However, even these methods are currently too time consuming to be applied cost-effectively at regional scales (Lobell et al 2010). Therefore, there is a need for the development of more practical (i.e., quicker and cheaper) methods and tools to determine and evaluate soil salinity in order to improve decision-making processes.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of spectral reflectance of high soil bulk density (compacted) soils was higher than for low density (non-compacted) soils due to changes in soil structure and porosity. Lobell et al (2009) found the multi-year average MODIS EVI coupled with local information captured one-third to one-half of the spatial variation of soil salinity. Rogovska and Blackmer (2009) described a significant correlation between Green-NDVI and soil acid (pH) and calcium carbonate equivalent in areas of the US Corn Belt.…”
Section: Soil-based Ecosystem Servicesmentioning
confidence: 96%
“…Salinization can occur naturally, through aerosolization, deposition, or contact with sea salts in coastal locations [120], or through proximity to saline seeps, shallow water tables, and degradation of parent rock materials inland [121,122]. Alternatively, so-called "secondary salinization" occurs anthropogenically, as a result of replacing deep-rooted native vegetation with shallow-rooted crops and pasture or from adding irrigation water to soils [120,123].…”
Section: Salt Stressmentioning
confidence: 99%